MANAJEMEN PENDIDIKAN KARAKTER DALAM MEMBENTUK GENERASI BERINTEGRITAS ERA GLOBALISASI DI SMK DARUSSALAM BLOKAGUNG BANYUWANGI - Hidayatullah, Nur; Nadir, Mirhabun (Universitas Islam Negeri (UIN) Sumatera Utara, 2024)
The purpose of this study is to analyze in depth how character education management is implemented at SMK Darussalam Blokagung Banyuwangi in forming a generation with integrity amidst the challenges of globalization. This study uses a qualitative case study approach at SMK Darussalam Blokagung Banyuwangi to understand character education management in depth. Informants were selected purposively, including the principal, teachers, supervisors, and students. Data were collected through observation, in-depth interviews, and documentation, then analyzed using the Miles and Huberman model (reduction, presentation, drawing conclusions). Data validity was maintained through triangulation of sources and techniques to ensure the validity of the research results. The results of this study indicate that the success of character education at SMK Darussalam Blokagung Banyuwangi is supported by the visionary and transformational leadership of the principal as a moral role model. The synergy between teachers, dormitory supervisors, and parents creates a comprehensive and consistent character education ecosystem in various student environments. Periodic data-based evaluations are effective monitoring tools to measure character development and provide feedback for appropriate coaching. Integration of leadership, multi-party collaboration, and a structured evaluation system ensures that character education runs optimally, producing graduates with high integrity and who are ready to face the challenges of globalization